Preserving earth’s flora in the 21st century: climate, biodiversity, and global change factors since the mid-1940s - Mosoh, Dexter Achu; Prakash, Om; Khandel, Ashok Kumar; Vendrame, Wagner A. (Frontiers in Conservation Science, 2024)
Climate change and biodiversity conservation are two of the twenty-first century's most pressing issues. Global climate forecasts strongly suggest that the frequency and magnitude of climate-related events will increase, resulting in progressively severe global impacts, particularly on plant diversity. Despite the historic 2015 Paris Agreement, limiting global warming to 1.5 degrees Celsius and climate financing remain major issues today, with negotiations to meet these targets still ongoing. The National Biodiversity Strategic Action Plan (NBSAP), a mechanism of the Convention on Biological Diversity (CBD), has not been effectively implemented at the country level, and in some cases, these NBSAPs lack explicit biodiversity goals. This review presents a comprehensive view of these issues, with a particular emphasis on the challenges and shortcomings of current climate and biodiversity conservation policies or measures. It discusses the effectiveness of the Kew conservation strategy as a role model for effective plant diversity protection and conservation, as well as the critical role that Plant Tissue Culture technology (PTC) can play in the plant-related goals of the 30-by-30 post-2020 global biodiversity conservation framework, which is strongly support in this review. It concludes by proposing and elaborating on a Kew-Wide Mechanism (KWM) that can be used to aid climate change resilience, mitigate anthropogenic plant diversity loss, energize global plant conservation efforts, and accelerate ecosystem restoration while the global economy gradually decarbonizes.